The Effect of Family Support on the Relapse of Drug Abusers - Azwar, Muhammad Azwar; Arlin Adam; Lilis Widiastuty (Window of Health : Jurnal Kesehatan, 2025)
Drug abuse remains a persistent global health challenge, with relapse continuing to be a major obstacle in sustaining recovery after rehabilitation. This study examined the association between knowledge, motivation, and family support factors, including emotional, social, and moral support, with relapse among residents at the Community-Based Rehabilitation Institute of the Mitra Husada Foundation in Makassar. A cross-sectional design was applied, involving all 82 rehabilitation residents through total sampling. Data were collected using structured questionnaires and analyzed with Chi-Square and logistic regression tests. The results demonstrated significant associations between relapse and knowledge (p < 0.013), motivation (p < 0.0001), emotional support (p <0.004), social support (p = 0.002), and moral support (p < 0.0001). Logistic regression analysis identified motivation as the most influential factor (Wald = 8.026, p < 0.005). The study concludes that strengthening intrinsic motivation and consistent family involvement are essential strategies in relapse prevention. Integrating family-based aftercare programs into rehabilitation services is recommended to ensure sustainable recovery.